STEM Integration in Primary Education: A Review of Pedagogical Approaches and Student Outcomes - Reni Manovtri; Hafiz Hidayat; Weni Yulastri (Jurnal Penelitian Pendidikan IPA, 2025)
This research examines the pedagogical approaches used in integrating STEM into primary education, their impacts on student outcomes, and the challenges faced during implementation. The study reviewed 35 peer-reviewed articles published between 2010 and 2023, focusing on three key themes: pedagogical approaches, student learning outcomes, and implementation barriers. Findings reveal that Project-Based Learning (PjBL), Problem-Based Learning (PBL), Inquiry-Based Learning (IBL), and technology-enhanced learning are the most effective methods for STEM integration. These approaches significantly improve students' scientific literacy, critical thinking skills, and interest in STEM, particularly among underrepresented groups such as girls and students from low-income backgrounds. However, challenges such as inadequate teacher training, resource constraints, and curriculum misalignment hinder successful implementation. The study underscores the need for professional development programs, increased funding for STEM resources, and curriculum reforms to address these barriers. The results align with constructivist learning theories, emphasizing active, hands-on learning experiences. Future research should focus on equity, technology integration, and innovative teacher training models to enhance STEM education. This review provides valuable insights for educators, policymakers, and researchers aiming to advance STEM education in primary schools and prepare students for 21st-century challenges.